A Mössbauer study of DyCrO4 and ErCrO4 - G. A. Stewart; J. M. Cadogan; W. D. Hutchison; D. H. Ryan (AIP Advances, 2019)
Earlier Mössbauer investigations of rare earth chromates RCrO4 with R = Gd and Tm were interpreted in terms of a superposition of two sub-spectra (approx. 4:1 area ratio), despite there being only a single crystallographic R(4a) site. In addition, the magnetic transitions exhibited first-order character, which is contrary to bulk magnetic measurements. However, new 161Dy and 166Er Mössbauer data presented here for DyCrO4 and ErCrO4 show the expected single rare earth site in both cases and a conventional second order behaviour for ErCrO4.